BUMBA MEU BOI DO MARACANÃ: um estudo no currículo de Artes Visuais do Ensino Médio no Centro de Ensino Renato Archer em São Luís- MA - SOARES, Herbia Araujo (2024)
The research addresses Bumba meu boi do Maracanã in the Visual Arts Curriculum of High School in São Luís- Maranhão. The research site investigated was the Centro de Ensino Renato Archer high school, which is located in the Maracanã neighborhood. The general objective of the research was to investigate the integration of Bumba meu boi do Maracanã into the Visual Arts curriculum at the Renato Archer Teaching Center, with the purpose of understanding how this cultural manifestation can enrich and improve teaching, including it as content in a Pedagogical Didactic Guidelines Guide. The central question of the research was how is Bumba meu boi do Maracanã present in the Visual Arts curriculum in high school at the Renato Archer Teaching Center? The Dissertation is divided into six sections, namely: the Introduction; Historical Aspects of the Festa do Boi; Approaching Maracanã with Bumba meu boi; The Presence of Bumba meu boi in the Curriculum; Bumba meu boi do Maracanã in Art Classes at the Renato Archer Teaching Center, and finally the Final Considerations. In the section that deals with Bumba meu boi do Maracanã in Art Classes at the Renato Archer Teaching Center, we initially describe a detailed characterization of the school researched, then we discuss the methodological path of the Dissertation, then we develop the analyzes and interpretations of the research subjects articulating the theoretical axes established in the investigation and continuing to describe the educational product, which was a Pedagogical Didactic Guide. The Guide is made up of five chapters, excluding the Presentation and the Glossary. We proposed activities in each chapter, with video tips, readings, visits and workshops. Due to Covid- 19, we do not apply the educational product at the selected school. We are anchored in Normative Instruction No. 04/2020/PPGEEB/UFMA, which made the applicability of the educational product optional. The bibliographic sources that supported the research were: Azevedo Neto (1977); Barros (2019); Carvalho (1995; 2005); Cascudo (1972); Lima (2003); Reis (2005), Apple (1979); Arroyo (2015); Goodson (1995); HALL (1997), Bourdieu (1996), Candau (2011), Ana Mae Barbosa (1999), among others. The data collection instruments used were observation, semi-structured interviews with the assistant manager and an Art teacher. The research concluded that the Pedagogical Didactic Guidelines on Bumba meu boi do Maracanã in Art Classes can contribute to meeting the teaching and learning needs not only at the Renato Archer Teaching Center, but also for other schools in the Maracanã neighborhood.